2014
DOI: 10.1515/ip-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating while justifying intercultural requests

Abstract: Research into the speech-act request performed by people of different cultures operationalized at levels including nation, community of practice, and L2 speakers has identified and discussed sets of culture-related request-making behaviors. The findings of this research suggest that differences exist among cultures in request-making behaviors concerning the use and choice of request directness and strategies, rhetorical approaches, and internal and external modifications. The present study, with an intercultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…There are a large number of studies on the speech act of request (Blum-Kulka & Olshtain's, 1984; Taguchi, 2007; Al- Gahtani & Roever, 2012;Han, 2013;Langer, 2013;Ho, 2014). Moreover, their study focuses vary from various pragmatic strategies used to realize the request to different individual's specific strategy use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are a large number of studies on the speech act of request (Blum-Kulka & Olshtain's, 1984; Taguchi, 2007; Al- Gahtani & Roever, 2012;Han, 2013;Langer, 2013;Ho, 2014). Moreover, their study focuses vary from various pragmatic strategies used to realize the request to different individual's specific strategy use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another genre that has also gained considerable research attention is the business genre (e.g. Ho, 2014; Vergaro, 2004; Yeung, 2007). The promotional genre and its ‘colonies’ (Bhatia, 2004: 57) have also been researched extensively (e.g.…”
Section: Genre and Genre Analysis Researchmentioning
confidence: 99%
“…Unquestionably, research has also demonstrated how professionals achieved their various communicative purposes with genres in their workplace. For example, teachers, business personnel and computer programmers could get their professional colleagues to perform an act with request e-mails (Ho, 2011, 2014), marketing professionals could persuade potential customers to purchase a product or a service with sales promotion letters (Vergaro, 2004) and academics could disseminate research findings and establish academic credentials with research articles (Lin and Evans, 2012).…”
Section: Genre and Genre Analysis Researchmentioning
confidence: 99%
“…Outside of the academic community, it has also been demonstrated that evaluative language can be a resource for professionals to do face work while performing the face-threatening speech act request. In his study of the discourse of request emails in an intra-cultural context (Ho 2014a) and an inter-cultural context (Ho 2014b), it has been shown that while Chinese and non-Chinese professionals justify their requests, they also use evaluative language in an attempt to mitigate the face-threat caused by their act of requesting. Following Ho (2014a), I will draw upon Martin and White's (2005) appraisal theory as the analytical framework.…”
Section: Accreditationmentioning
confidence: 99%